Pessimism in Charles Simic’s Selected Poems - Raihan Naufal Fauzy Medy (Institut Seni Indonesia Yogyakarta, 2026)
Pessimism is an attitude of hopelessness toward existential meaning where it is having the tendency to see the bad side of things. This study explores how pessimism is presented in Charles Simic’s Selected Poems and what is the significance of pessimism is in the selected poems. This study applies qualitative research using Michael Riffaterre’s semiotic of poetry to analyze pessimism in three of Charles Simic’s selected poems, “The Grass”, “The Prompter”, and “Evening Walk.” Through heuristic and hermeneutic readings, the research identifies ungrammaticalities and reconstructs hypograms to uncover deeper layers of meaning. The findings reveal that Simic’s poetry emphasizes pessimism by writing it using metaphor and simile in free verse.These semiotic structures articulate a worldview where beauty and despair coexist, and where human efforts to find meaning are often met with silence or futility. His minimalist style amplifies this pessimism, rendering it both intimate and universal. Keyword: Pessimism, Charles Simic, Poems, semiotic of poetry